Evaluation of the Effectiveness of the Implementation of the Enterprise Resource Planning (ERP) System on the Financial Reporting Process of PT Telecommunications Company. (E-Jurnal Akuntansi, 2026)
This study aims to evaluate the effectiveness of the ERP system implemented at PT ABC, one of the largest telecommunications companies in Indonesia. This evaluation is important to ensure the ERP system provides optimal benefits for the company. This research uses a qualitative method with triangulation analysis through interviews with 5 resource persons and document analysis related to ERP. The Delone and Mclean model is used to assess system effectiveness based on five main aspects: System Quality, Information Quality, Service Quality, User Satisfaction, and Net Benefit. The results showed that the ERP system at PT ABC was effective in the aspects of System Quality, Information Quality, User Satisfaction, and Net Benefit. However, the Service Quality aspect still needs to be improved through further training. The advantage of this research is a comprehensive approach that assesses ERP effectiveness not only from the technical side, but also user satisfaction and business benefits.
Keywords: Enterprise Resource Planning (ERP); Delone and Mclean; Financial Report; Information System